Thematic Tafsir Studies in Islamic Education: An Analysis of Objectives, Methods, and Students - Hafid, Hafid; Anwar, Cecep; Khomah, Isti; Anisa, Hafilda; Islahiah, A’idatul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
In the context of globalization and rapid social change, Islamic education needs to adapt to remain relevant. The basic concepts and ideas of Islamic education can be analyzed and developed from the basic sources of Islamic teachings, namely the Qur’an and sunnah. This article aims to further explore the purpose of education, educational methods and how learners can be actively involved in the learning process. This research uses literature study and thematic tafsir method by examining Qs. Adz-Dzariyat: 56, Qs. An-Nahl: 125, and Qs. An-Nahl: 78. Humans were created to worship Allah and fulfill their role as caliphs on earth. This emphasizes the importance of integration between spiritual, moral, intellectual, and social development in building individuals who are noble and beneficial to society. Humans are also born without any knowledge so it is important for them to study knowledge by utilizing the senses that Allah has created for them. One of the main objectives of thematic interpretation studies is to increase students’ understanding of Islamic teachings. With this approach, students are not only required to memorize verses, but also to understand the context and meaning contained therein. This is very important in shaping good character and noble morals. The results show that by understanding and applying the goals, methods, and concepts of learners based on the Qur’an, Islamic education is able to create a generation that is faithful, knowledgeable, and contributes positively to society and the progress of global civilization.